Supplement to Cheklist of Bryobionta of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Checklist of Bryobionta of Ukraine (2008) is supplemented by 15 species, whose data appeared after its publication. Of them 3 species of Marchantiophyta division – Riccia beyrichiana Hampe ex Lehm., Riccia crinita Hoffm., Riccia erinacea Schiffn and 12 species of Bryophyta division – Lazarenkia kozlovii (Lazar.) Boiko, Aulacomnium arenopaludosum Boiko, Bryum badium (Brid.) Schimp. Сampylopus introflexus (Hedw.) Brid., Fissidens exiguus Sull., Grimmia fuscolutea Hook., Myrinia pulvinata (Wahlendb.) Schimp., Plagiothecium ruthei Limpr., Pohlia proligera (Kindb.) Lindb., Schistidium elengatulum Blom, Syntrichia laevipila Brid., Zygodon dentatus (Limpr.) Kart.View Pohlia andrewsii J. Shaw must be excluded from Cheklist of Bryobionta of Ukraine.
Keywords: Bryophytes, cheklist, new species of mosses, brioflora of Ukraine.